Decreased mortality in coronavirus disease 2019 associated mucormycosis with aspirin use: a retrospective cohort study. Issue 12 (14th December 2022) - Shaikh, Z; Sarkar, S; Biswas, R; Adhikari, A; Hallur, V K; Parida, P K; Preetam, C; Pradhan, P; Samal, D K; Nayak, A; Chadaram, S; Das, K K; et al.
Abstract: Objective: Rhino-orbito-cerebral mucormycosis is a rapidly progressive disease with high mortality rates of about 60 per cent. The increasing incidence of rhino-orbito-cerebral mucormycosis in coronavirus disease 2019 patients in India and worldwide has become a matter of concern owing to the case fatality rate. This study explored the use of low dose aspirin in decreasing the mortality rate of coronavirus disease 2019 associated mucormycosis. Method: This was a retrospective observational study. Patients suffering from post-coronavirus disease 2019 mucormycosis were included in the study. Each patient was treated with surgical debridement and systemic amphotericin B. Low dose aspirin was added, and mortality rates were compared with the patients who did not receive aspirin. Results: The demographic data and rhino-orbito-cerebral mucormycosis staging between the two groups were not significantly different. There was a statistically significant difference in mortality outcomes between the two groups ( p = 0.029) and a 1.77 times higher risk of dying for patients not receiving aspirin. Kaplan–Meier survival indicated that patients receiving aspirin had better survival rates ( p = 0.04). Conclusion: Low dose aspirin improves survival rates in coronavirus disease 2019 associated mucormycosis.